A COMPARATIVE ANALYSIS OF TRANSCARDIAL PERFUSION TECHNIQUES FOR BRAIN FIXATION IN RODENTS: A CALL FOR STANDARDIZATION OF TRANSCARDIAL PERFUSION - Wahyudi, Dhyani Paramita; Makkiyah, Feda Anisah; Buana, Gherriandi Raja (The Health Researcher's Journal, 2025)
Transcardial perfusion is a crucial technique in rodent research for tissue fixation and preservation. The process typically involves flushing the vascular system with saline to remove blood, followed by fixation with 4% paraformaldehyde (PFA) or formalin. However, differences in species, procedural techniques, and fluid volumes can influence perfusion efficiency and tissue quality. This literature review compares six transcardial perfusion protocols used in mice and rats, focusing on procedural variations and fluid volume requirements. Data were collected from published protocols detailing perfusion techniques, obtaining evidence that substantial variability is observed in the protocols, including differences in anesthesia regimens, surgical approaches, perfusion techniques, fluid compositions, and fixation outcomes. Future research should focus on standardizing perfusion protocols to improve consistency in fixation quality, minimize tissue degradation, and preserve structural and molecular integrity.